1993
DOI: 10.1111/j.1399-302x.1993.tb00572.x
|View full text |Cite
|
Sign up to set email alerts
|

Modification of experimental Porphyromonas gingivalis murine infection by immunization with a polysaccharide‐protein conjugate

Abstract: To better understand the role of the capsular polysaccharide in the virulence of Porphyromonas gingivalis, the effect of immunization with a polysaccharide-protein conjugate on experimental murine infection was evaluated. The conjugate was prepared using polysaccharide isolated from P. gingivalis strain ATCC 53977 and bovine serum albumin. One group of 22 mice was immunized by intraperitoneal injection with the conjugate and a control group of 25 mice was similarly immunized with bovine serum albumin. Serum an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

1997
1997
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 27 publications
1
13
0
Order By: Relevance
“…The cell responses observed, such as early infiltration of neutrophils followed by macrophages and lymphocytes, were similar to those observed previously in infections in connective tissue (11,13,19,26) and peritoneal cavities (6, 10) after injection of various bacteria, including peritoneal injection with P. gingivalis (4,5,21,32,34). The present results also demonstrated that similar responses with slight differences were caused by intraperitoneal injection of equivalent amounts of Gram-positive E. saphenum (Fig.…”
Section: Discussionsupporting
confidence: 90%
“…The cell responses observed, such as early infiltration of neutrophils followed by macrophages and lymphocytes, were similar to those observed previously in infections in connective tissue (11,13,19,26) and peritoneal cavities (6, 10) after injection of various bacteria, including peritoneal injection with P. gingivalis (4,5,21,32,34). The present results also demonstrated that similar responses with slight differences were caused by intraperitoneal injection of equivalent amounts of Gram-positive E. saphenum (Fig.…”
Section: Discussionsupporting
confidence: 90%
“…gingivulis polysaccharide reduced the severity of infection, but could not prevent invasive infection with I? gingivulis (202). Genco et al (71) analyzed phenol-water extracts from I!…”
Section: F! Gingivalismentioning
confidence: 99%
“…Immune responses elicited to capsular polysaccharides of P. gingivalis decreased tissue destruction initiated by P. gingivalis infectious challenge (Schifferle et al, 1993). Other investigations (Evans et al, 1992a;Kusumoto et al, 1993) demonstrated the ability of antibody to interfere with fimbrial function (adherence of P. gingivalis to oral tissues) in colonization and subsequent disease related to infection by P. gingivalis.…”
Section: Whole Cells From Porphyromonas Gingivalismentioning
confidence: 97%